PARTISIPASI REMAJA SMA DALAM PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) DI KECAMATAN SUKOHARJO - -, indah rahmawati; wati, Yuli Kusuma (STIKES Muhammadiyah Klaten, 2011)
Participation of Senior High School Adolescent in Prevention to Dengue Fever (DBD) in Sukoharjo District Â ABSTRACT Â Sukoharjo of district is represent the district of endemis DBD with amount of case in year 2006 counted 40 patient summed uply is resident of equel 85,545 (IR=4,67) in 10.000 resident) and accupy the third sequence after district of Kartosura and Grogol. This research is am to know the relation between knowlege, attitude, fomentation of health officer, family fomentation, will experience with addescent participation of SMA in prevention DBD. The of observasional research with the device of cross sectional. The subject of the research is adolescent which hace age between 15-18 year which go to school in Senior High School I Sukoharjo and Islamic Senior High School I Sukoharjo. Population is counted 1093 adolescent. Sample is counted go adolescent which is convering class I and class II with Sample Random Sampling Technique. The conclusion there are no relation between knowledge, attitude, fomentation of health officer will experience with the adolescent participation of SMA in preventation DBD of adolescent in Sukoharjo district. The are no relation between family fomentation with the adolescent participation of Senior High School in prevention DBD of adolescent in Sukoharjo district. Â Key word : Participation of Senior High School Adolescent, Prevention to Dengue (DBD)